Familia y participación económica en la crianza infantil: un estudio de las mujeres de la florícola Luxus Blumen, 2024. - Falcón Villafuerte Nayeli Carolina (2025)
This topic investigates the impact of women's economic participation in the "Luxus Blumen" flower farm on their role as caregivers. Female workers face significant challenges in balancing long working hours with family responsibilities, which affects both their well-being and that of their children. Previous studies highlight the precariousness of work in the flower sector and its relationship with child development and the health of female workers. The research is justified by recognizing the importance of valuing women's work, not only for their economic contribution, but also for their influence on the emotional and social development of children. A mixed methodology will be used that will combine surveys and semi-structured interviews, allowing for a deep understanding of female workers' experiences and family dynamics. This approach will facilitate the identification of areas for improvement in labor policies that favor the reconciliation between work and family life. The results are expected to provide a comprehensive insight into how working conditions affect childcare, as well as strategies to promote equity in both the workplace and the home. Additionally, the study aims to understand the challenges faced by working women and contribute to changes in social perceptions and policy formulation to improve their living and working conditions. Keywords: female, floriculture, care, labor precariousness, equity.